Penerapan Model ARIMA Dalam Memprediksi IHSG - Bambang Hendrawan (JURNAL INTEGRASI, 2012)
The objective of this research is seeking the best performance of ARIMA Model to predict Indonesia Composite Index (IHSG) in Indonesia Stock Exchange. The data were acquired from IDX weekly statistics published by Indonesia Stock Exchange during 95 weeks. The method used for analysis was Box & Jenkins Method with iterative approach and using E-views Application. The result of this research indicates that the model that can be applied to predict the IHSG is ARIMA (2,1,2).